STUDI PENENTUAN LOKASI EVAKUASI VERTIKAL DI PANTAI PARANGTRITIS - , Arkadia Rhamo ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Parangtritis beach countenances directly to Indian Ocean. The boundary of the Eurasian and the Indo-Australian plates located in the Indian Ocean allows vertical dislocation of the Earth's plates that trigger a tsunami wave on the beach. One of mitigation efforts against the tsunami is providing a place for evacuation. The existence of vertical evacuation construction is expected to reduce the risk of death. The location for evacuation was determined by conducting a tsunami evacuation simulation (SET) using Evacuware Version 1.0 software. The simulation was carried out through three scenarios types. The first scenario was applied to the existing final refuge site (TPA). The second scenario divided the evacuation area to determine which TPA would be less reachable. The third scenario was conducted by adding alternative vertical evacuation construction in the simulation. The research results indicate that the effective vertical evacuation construction location is in the market area that is at coordinates: 49S 425983mT 9113180mU, located at 12.5 masl and within 320 m from the beach. The additional vertical evacuation construction could reduce the number of fatalities. An increasing number of human survivors reach 7.18% for the simulation of 4,000 people, 19.16% for 7,000 people, and 31.75% for the number of 10,000 people.